Physiological profile of age-group wrestlers - Terbizan, D. J.; Seljevold, P. J. (The Journal of Sports Medicine and Physical Fitness, 1996)
This research compares the physiological characteristics of young wrestlers grouped by age. Three hundred and twenty eight wrestlers (mean age 15.99 +/- 1.08 years and mean weight 65.94 +/- 11.01 kg) attending a wrestling training camp between 1990 and 1994 were tested to determine their physiological capacities. The physiological profile included body weight, body composition measured by hydrostatic weighing, sum of skinfolds, aerobic power, grip strength, absolute and relative endurance, situps, pushups, fatigue, and flexibility measures. Wrestlers were divided into three age categories: G1: < or = 15 years of age; G2: 16 years of age; and G3: > or = 17 years of age. Analysis of variance with Tukey post hoc test revealed statistically significant (p < 0.05) differences in body weight (G1 < G2,G3), fat free weight (G1 < G2,G3), grip strength (G1 < G2,G3), absolute (G1 < G2,G3; G2 < G3) and relative endurance (G1 < G3,G2 < G3), pushups (G1 < G3; G2 < G3), sit and reach (G1 < G3), Margaria-Kalamen power (G1 < G2,G3), and Wingate arm and leg mean powers (G1 < G2,G3). When covaried for body weight and fat free weight, there were no significant differences in grip strength and Margaria-Kalamen power. Significant differences in arm mean power when covaried for body weight and fat free weight (G1 < G3) and for leg mean power when covaried for body weight (G1 < G3) were noted. These wrestlers were similar to young wrestlers in published research, with low body fat, excellent aerobic capacity and flexibility. When separated by age, the younger wrestlers possess less body weight, fat free weight, grip length, and power measures, possibly due to lower muscle mass.